Untamed Narratives: Male Homoeroticism in Central Americal Literary Production Between the 20th and 21st Centuries - Arévalo, Amaral (2026)
Central American narratives, despite their contributions to literature, have been categorized as peripheral literary production, and homoerotic aesthetics within them are under-recognized. The objective of this text is to analyze the theme of homoeroticism in Central American literary production (novels, short stories, poetry and theater). A documentary analysis of the literary output and specialized academic material was used as a methodology. The analytical perspective developed to analyze a selected series of Central American literary productions integrates three dimensions: homointertextuality, homotextualization and homopoetics. The result is that homointertextuality reveals that traditional discourses pathologized and criminalized homoerotic desires in the early 20th century, forcing them to manifest in a dehumanized manner. Homotextualization presented discursive strategies such as necrorepresentation and mechanisms of political, cultural, and social repression that attempted to censor homoerotic aesthetics. This aesthetics managed to infiltrate and resist, escaping through voices that challenged normative control during political repression and internal wars. Finally, in the 21st century, in homopoetics, homoerotic identity became legitimate. Desire ceased to be subterranean and asserted itself with autonomy and pride in societies where discrimination and violence against LGBTIQA+ people persist.